DETEKSI CEMARAN BAKTERI PADA CINCAU HITAM YANG DIKEMAS DAN TIDAK DIKEMAS METODE KULTUR - Evy Ratnasari Ekawati; Muhammad Sungging Pradana; Theresia Pao (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2022)
The black cincau is a widely consumed food by the community. The black cincau used is the leaves and stems, which can produce more grass jelly extract. The community can use the black cincau plantto treat digestive disorders. This research aims to detect bacterial contamination by comparing packaged and unpackaged black cincau sold in the market. This study was an experimental study using the bacterial culture method. In this study, six samples were purchased from the supermarket, and seven pieces were purchased at the traditional market. After that, isolation and identification of bacteria were carried out on packaged and unpackaged black cincau. From 6 samples of black cincau that were packaged and unpackaged, it was detected that Salmonella sp. and Klebsiella sp. Simple ways to reduce contamination of black cincau include using clean water, cooking food thoroughly, and using clean containersKeywords: Detection bacteria, contamination, black cincau, culture